Letter (copy) : Situation in Spain - Tewson, Vincent
010-0154-001 DMS. HVT/FC/827. Secretary's. 4th August, 1936. Mr. W. J. R. Squance, General Secretary, The Associated Society of Locomotive Engineers and Firemen, 9, Arkwright Road, Hampstead, N.W.3. Dear Mr. Squance, SITUATION IN SPAIN I have your letter of 31st July in regard to correspondence you have received from the International Transportworkers' Federation on the above subject. This is receiving attention and as soon as I have anything to report I will write to you again. Yours sincerely, Assistant secretary. 292/946/10/167